PENGARUH KEBIJAKAN MONETER DAN FISKAL TERHADAP PEMBANGUNAN EKONOMI - Indaniaty Hasanah Sari; Khayriza Sinambela (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Monetary is a part of economics which studies the nature of money and its influence on economic activities. Monetary policy is a medium used by the Central Bank to manage various financial variables such as the rupiah exchange rate and interest rates. And the main goal is none other than to achieve currency stability both from internal and external factors. Fiscal policy is referred to as the management of the government budget in influencing the economy, for example policies in taxation that is collected and collected, transfer payments, and that includes government. The aim of fiscal policy is to achieve stability/balance of income with expenditure, stimulate economic growth, and overcome problems such as income inequality and unemployment.